Small area variations and factors associated with blood pressure and body-mass index in adult women in Accra, Ghana: Bayesian spatial analysis of a representative population survey and census data - Sierra N. Clark; James E. Bennett; Raphael E. Arku; Allan G. Hill; Günther Fink; Richard M. Adanu; Richard B. Biritwum; Rudolph Darko; Ayaga Bawah; Rosemary B. Duda; Majid Ezzati (PLoS Medicine, 2021)
Background Body-mass index (BMI) and blood pressure (BP) levels are rising in sub-Saharan African cities, particularly among women. However, there is very limited information on how much they vary within cities, which could inform targeted and equitable health policies. Our study aimed to analyse spatial variations in BMI and BP for adult women at the small area level in the city of Accra, Ghana. Methods and findings We combined a representative survey of adult women’s health in Accra, Ghana (2008 to 2009) with a 10% random sample of the national census (2010). We applied a hierarchical model with a spatial term to estimate the associations of BMI and systolic blood pressure (SBP) and diastolic blood pressure (DBP) with demographic, socioeconomic, behavioural, and environmental factors. We then used the model to estimate BMI and BP for all women in the census in Accra and calculated mean BMI, SBP, and DBP for each enumeration area (EA). BMI and/or BP were positively associated with age, ethnicity (Ga), being currently married, and religion (Muslim) as their 95% credible intervals (95% CrIs) did not include zero, while BP was also negatively associated with literacy and physical activity. BMI and BP had opposite associations with socioeconomic status (SES) and alcohol consumption. In 2010, 26% of women aged 18 and older had obesity (BMI ≥ 30 kg/m2), and 21% had uncontrolled hypertension (SBP ≥ 140 and/or DBP ≥ 90 mm Hg). The differences in mean BMI and BP between EAs at the 10th and 90th percentiles were 2.7 kg/m2 (BMI) and in BP 7.9 mm Hg (SBP) and 4.8 mm Hg (DBP). BMI was generally higher in the more affluent eastern parts of Accra, and BP was higher in the western part of the city. A limitation of our study was that the 2010 census dataset used for predicting small area variations is potentially outdated; the results should be updated when the next census data are available, to the contemporary population, and changes over time should be evaluated. Conclusions We observed that variation of BMI and BP across neighbourhoods within Accra was almost as large as variation across countries among women globally. Localised measures are needed to address this unequal public health challenge in Accra. Sierra N. Clark and colleagues analyze spatial variations of blood pressure and body mass index, and associated factors in Ghanaian women. Author summary Why was this study done? The social, physical, and food environment influence the spatial distribution of noncommunicable diseases and their risk factors such as blood pressure (BP) and body-mass index (BMI) within and across neighbourhoods in cities. In sub-Saharan Africa (SSA), where cities are growing rapidly and BMI and BP have risen, there is limited information on within-city variation in cardiometabolic risk factors. This information could inform targeted and equitable public health programmes. What did the researchers do and find? We combined data from an epidemiological study that had randomly sampled women in Accra and geospatial data on roads and community biomass fuel use to understand how individual and household factors as well as residence predict BMI and BP. Data were analysed in a Bayesian spatial model and then used together with the data from the census to predict BP and BMI levels for all women in Accra. Local area variation in BMI and BP is large within Accra, similar to patterns seen in other cities and regions around the world. Average BMI was higher among women with higher socioeconomic status (SES), as measured by ownership of assets and household infrastructure. What do these findings mean? The spatial variations in BMI and BP across neighbourhoods in Accra were almost as high as variation seen between countries. Localised public health actions can help address these disparities and reduce the resulting overall public health burden.